ТЕАТР-ТОМОША ТАДБИРЛАРИДА МУСИҚАДАН ФОЙДАЛАНИШНИ РЕЖАЛАШТИРИШ - Ешбаева, Г. (SCIENCE and SOCIETY, 2022)
The attention paid to the organization of holidays in our country. Holidays as one of the main parts of cultural events are reaching all homes of the country. Great attention is paid to the organization of celebrations at a high level in cultural institutions and art venues, as well as in organizations that do not belong to the field of art or culture in general.
Keywords: culture; holidays; art; music; status; brochures; activity-plans